2019
DOI: 10.7189/jogh.09.020427
|View full text |Cite
|
Sign up to set email alerts
|

Status of health information exchange: a comparison of six countries

Abstract: BackgroundHealth information exchange (HIE) is frequently cited as an important objective of health information technology investment because of its potential to improve quality, reduce cost, and increase patient satisfaction. In this paper we examine the status and practices of HIE in six countries, drawn from a range of higher and lower income regions.MethodsFor each of the countries represented – China, England, India, Scotland, Switzerland, and the United States – we describe the state of current practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…The proposed model offers hospitals a focused EHR development model that can positively impact the adoption and use of EHRs by overcoming information system design barriers and contribute to improved data quality and data use. 22 The study findings and the proposed HDX model fulfill the requirements for a health information exchange (HIE) outlined in a recent study, 21 which compared the status of HIEs in six countries, including India. The study used exemplar HIE scenarios focusing on the transfer of care and referral, and mentioned that HIE requires electronic medical record systems or other systems to gather clinical information (at both the point of capture and at the recipient organizations), incentives, secure networks for HIE, and appropriate policy and regulatory environments.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The proposed model offers hospitals a focused EHR development model that can positively impact the adoption and use of EHRs by overcoming information system design barriers and contribute to improved data quality and data use. 22 The study findings and the proposed HDX model fulfill the requirements for a health information exchange (HIE) outlined in a recent study, 21 which compared the status of HIEs in six countries, including India. The study used exemplar HIE scenarios focusing on the transfer of care and referral, and mentioned that HIE requires electronic medical record systems or other systems to gather clinical information (at both the point of capture and at the recipient organizations), incentives, secure networks for HIE, and appropriate policy and regulatory environments.…”
Section: Discussionmentioning
confidence: 74%
“…Although an effective and efficient electronic HDX is an important health system strengthening goal for most countries, there is wide variation in what countries have been able to achieve, especially in LMICs like India. 21 The HDX model presented here shows how different workflows in hospitals can be connected through an EHR network to create an EHR for a patient. The EHR network can integrate patient data from administrative, billing, clinical, nursing, laboratory, pharmacy, and radiology systems.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies have cited several limitations and barriers to implementing and maintaining HIE systems. [33][34][35][36] However, most previous HIE studies have been observational, which has the potential to underestimate benefits due to selection bias and confounding influences. Conversely, RCTs have suggested that HIE can improve health care delivery by identifying medication discrepancies, previous test results, and changes in various clinical parameters over time.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increasing demand for exchanging electronic health records and medical images has made the growth of healthcare information networks indispensable. Many countries have built [17][18][19] or are developing [20][21][22] their national healthcare information network. Such a system provides a common platform for information exchange across diverse healthcare entities.…”
Section: Introductionmentioning
confidence: 99%